Induction and enhancement of platelet aggregation in vitro and in vivo by model polystyrene nanoparticles - Smyth,E; Solomon,A; Vydyanath,A; Luther,PK; Pitchford,S; Tetley,TD; Emerson,M (Nanotoxicology, 2014)
Abstract Nanoparticles (NPs) may come into contact with circulating blood elements including platelets following inhalation and translocation from the airways to the bloodstream or during proposed medical applications. Studies with model polystyrene latex nanoparticles (PLNPs) have shown that NPs are able to induce platelet aggregation in vitro suggesting a poorly defined potential mechanism of increased cardiovascular risk upon NP exposure. We aimed to provide insight into the mechanisms by which NPs may increase cardiovascular risk by determining the impact of a range of concentrations of PLNPs on platelet activation in vitro and in vivo and identifying the signaling events driving NP-induced aggregation. Model PLNPs of varying nano-size (50 and 100 nm) and surface chemistry [unmodified (uPLNP), amine-modified (aPLNP) and carboxyl-modified (cPLNP)] were therefore examined using in vitro platelet aggregometry and an established mouse model of platelet thromboembolism. Most PLNPs tested induced GPIIb/IIIa-mediated platelet aggregation with potencies that varied with both surface chemistry and nano-size. Aggregation was associated with signaling events, such as granule secretion and release of secondary agonists, indicative of conventional agonist-mediated aggregation. Platelet aggregation was associated with the physical interaction of PLNPs with the platelet membrane or internalization. 50 nm aPLNPs acted through a distinct mechanism involving the physical bridging of adjacent non-activated platelets leading to enhanced agonist-induced aggregation in vitro and in vivo. Our study suggests that should they translocate the pulmonary epithelium, or be introduced into the blood, NPs may increase the risk of platelet-driven events by inducing or enhancing platelet aggregation via mechanisms that are determined by their distinct combination of nano-size and surface chemistry.